Optimized approaches to the diagnostics of Mycosis Fungoides - I. A. Kuklin (Лечащий Врач)
The article presents optimized approaches to the diagnostics of Mycosis Fungoides. The clinical and anamnestic signs, allowing to suspect Mycosis Fungoides at the clinical stage of the diagnostics, are presented. An innovative method of non-invasive preliminary diagnostics using reflectance confocal microscopy of the skin is described. A rational scheme of examination of patients with suspected Mycosis Fungoides, using new information technologies for registration and monitoring of patients is proposed.